The Use of Scientific Writing Heuristics (SWH) to Build Rebuttal Abilities in Scientific Argumentation - Anisa Anisa; Ari Widodo; Riandi Riandi; Muslim Muslim (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
The research aims to build and measure students' abilities in rebuttal using the Scientific Writing Heuristic (SWH) approach. This mixed-method research method was carried out for 5 months on 38 students, at a high school in West Java, Indonesia. The issue of socio-scientific genetics is given the theme of Genetic Modified Organisms with rebuttal measurements using the updated Toulmin argumentation framework. Qualitative and quantitative data are taken in this article in the form of argumentation before, during, and after treatment; coupled with deep interviews and questionnaires as well as observation of discussions. The results showed there were changes and improvements in rebuttal ability by 27.15% (30 students). The distribution of the strength of evidence is at most level 2 at 48.7% with a weak category, at level 3 at 30.8% with a strong enough category, at level 4 at 20.5% with a strong category.